PURCHASE INTENTION AND PURCHASE DECISION MODEL: MULTI CHANNEL MARKETING AND DISCOUNT ON MEDCOM.ID ONLINE NEWS PORTAL - Al Hafizi, Nasikhul Amin; Ali, Hapzi (Dinasti Publisher, 2021)
This study aims to determine the effect of multi-channel marketing and discount / saving value on purchasing decisions through clients' buying interest in advertising services provided by Medcom.id. The numbers of respondents involved in this study were 85 respondents. All respondents are clients (agencies or companies) who have advertised on Medcom.id. The data in this study were analyzed quantitatively using the Partial Least Square technique with the help of the Smartpls program. The research results are: (1) Multi-channels marketing has a positive effect on the purchase interest of prospective clients, the better the multi-channel marketing conducted by Medcom.id, the higher the buying interest of prospective clients to advertise on Medcom.id; (2) Discount has a positive and significant effect on consumer buying interest, the more attractive the discount Medcom.id offers, the higher the buying interest of potential clients to advertise on Medcom.id; (3) Multi-channels marketing has a positive effect on client purchasing decisions, the better the multi-channel marketing conducted by Medcom.id, the higher the purchasing decisions of prospective clients to advertise on Medcom.id; (4) Discount has a positive and significant effect on consumer purchasing decisions, the more attractive the discount offered by Medcom.id, the higher the purchasing decisions of prospective clients to advertise on Medcom.id; (5) Purchasing interest affects consumer purchasing decisions, prospective clients with high buying interest tend to have high purchasing decisions for advertising services offered by Medcom.id; (6) Purchasing interest can mediate the effect of multi-channels marketing on purchasing decisions, the better multi-channels marketing will increase client's buying interest which in turn will improve purchasing decisions; (7) Purchase interest can mediate the effect of discount on purchasing decisions, giving discounts that attract prospective clients will increase prospective clients' buying interest which in turn will increase client purchasing decisions.